RNA Hydrogel Combined with MnO2 Nanoparticles as a Nano-Vaccine to Treat Triple Negative Breast Cancer - Wang, Weicai; Liu, Xiaofan; Ding, Lairong; Jin, Hyung Jong; Li, Xuemei (Frontiers in Chemistry, 2021)
Hypoxia is not only the reason of tumor metastasis but also strengthen the spread of cancer cells from the original tumor site followed by growth of next tumors and resulting cancer recurrence. Herein, we developed a self-assembled RNA hydrogel that efficiently delivered synergistic DNA CpG and short hairpin RNA (shRNA) adjuvants, as well as MnO2 loaded-photodynamic agent chlorine e6 (MnO2@Ce6), and a chemotherapy drug doxorubicin (DOX) into MDA-MB-231cells. The RNA hydrogel consists of one tumour suppressor miRNA (miRNA-205) and one anti-metastatic miRNA (miRNA-182), both of which showed an outstanding effect in synergistically abrogating tumours. The hydrogel would be dissociated toward endogenous Dicer enzyme to release loaded therapeutic molecules, and in the meantime induce decomposition of tumor endogenous H2O2 to relieve tumor hypoxia. As a result, a remarkable synergistic therapeutic effect is achieved through the combined chemo-photodynamic therapy, which simultaneously triggers a series of anti-tumor immune responses. Besides, the hydrogel as the carrier which modificated aptamer to targeted MDA-MB-231 has the advantage of good biocompatibility and low cytotoxicity. This strategy could be implemented to design form any other microRNA (miRNA) as the carrier and combined other treatment methods to treat many other human cancers, which overcomes current limitations of cancer therapies.